Preoperative screening and intervention for mild anemia with low iron stores in elective hip and knee arthroplasty. Issue 12 (6th November 2017) - Pujol‐Nicolas, Andrea; Morrison, Rory; Casson, Clare; Khan, Sameer; Marriott, Allan; Tiplady, Christopher; Kotze, Alwyn; Gray, William; Reed, Mike
Abstract : BACKGROUND: Preoperative anemia in patients undergoing elective hip and knee arthroplasty is associated with increased postoperative morbidity and mortality, red blood cell (RBC) transfusion, and length of stay (LOS). The aim of this study was to assess the effect of optimizing hemoglobin (Hb) levels before elective primary hip and knee arthroplasty. STUDY DESIGN AND METHODS: This is a prospective comparative cohort study of patients who underwent elective hip and knee arthroplasty before (control) and after (intervention) the launch of a Hb optimization program. Patients with anemia followed an agreed upon algorithm dependent on their medical history and blood variables taken on listing for surgery. The primary outcome for this study was the requirement for allogenic RBC transfusion. Secondary outcomes included hospital LOS, admission to critical care, readmission, medical complications, incidence of thromboembolic events, mortality, and costs. RESULTS: A total of 1814 control patients operated between February 2012 and February 2013 were compared to 1622 intervention patients operated between February 2013 and May 2014. In the intervention group transfusion was significantly reduced (108 [6%] vs. 63 [4.1%], p = 0.005) as well as readmission (81 [4.5%] vs. 48 [2.3%], p= 0.020) and critical care admission (23 [1.3%] vs. 9 [0.5%], p = 0.030). LOS was significantly reduced from 3.9 days to 3.6 days (p = 0.017). The saving for the cohort was £263, 000 (342, 000). CONCLUSIONS: Algorithm‐led preoperative anemia screening and management in elective arthroplasty was associated with reduced RBC transfusion, readmission, critical care admission, LOS, and costs.